2016
DOI: 10.1016/j.fertnstert.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous fertility and in vitro fertilization outcome: new evidence of human papillomavirus sperm infection

Abstract: A reduction in natural and assisted cumulative pregnancy rate and an increase in miscarriage rate are related to the presence of HPV at sperm level. Although the exact mechanism by which sperm infection is able to impair fertility remains unclear, this aspect is worthy of further investigations. If confirmed, these results could change the clinical and diagnostic approach to infertile couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 27 publications
3
96
0
5
Order By: Relevance
“…Indeed, our data indicated that unvaccinated women with a history of STI/PID had appreciably lower fecundability; those vaccinated with a history of STI/PID had similar fecundability to unvaccinated women without a history of STI/PID. These findings agree with the animal literature demonstrating no adverse effects of HPV vaccination on rat fecundability and with the human literature finding adverse effects of HPV infection on fertility …”
Section: Commentsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, our data indicated that unvaccinated women with a history of STI/PID had appreciably lower fecundability; those vaccinated with a history of STI/PID had similar fecundability to unvaccinated women without a history of STI/PID. These findings agree with the animal literature demonstrating no adverse effects of HPV vaccination on rat fecundability and with the human literature finding adverse effects of HPV infection on fertility …”
Section: Commentsupporting
confidence: 92%
“…Detectable HPV infection among males has been associated with reduced sperm motility, increased antisperm antibodies, and lower pregnancy rates in studies of infertile couples; another study found no effect on semen quality . Among females undergoing intrauterine insemination, 1.9% with detectable HPV infection conceived compared with 11.4% without the virus .…”
mentioning
confidence: 97%
“…After the removal of 10 records as duplicates and screening of 92 through their abstracts, 38 studies were identified as possibly eligible for inclusion and retrieved as full texts. Of these, 24 studies were excluded (Table S1), two studies were ongoing 15,16 , two of those eligible were not used in the meta-analysis owing to a lack of data of interest 17,18 and 10 that met the qualitative and quantitative criteria for inclusion in our meta-analysis were selected 6,7,[19][20][21][22][23][24][25][26] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Men producing sperm within the normal Cap-Score range and failing to generate pregnancy within two IUI cycles might be producing sperm that lack the ability to initiate embryo development (Swann, Saunders, Rogers, & Lai, 2006;Yoon et al, 2008). As yet another alternative, recent evidence suggests that although there is little association between the presence of seminal human papillomavirus and semen analysis parameters (Luttmer et al, 2016), men with this infection have reduced ability to generate pregnancy (Garolla et al, 2016). The infected sperm are still able to gain access to oocytes and fertilize (Foresta et al, 2011), but appear to have an early reduction in embryo viability beyond that event.…”
mentioning
confidence: 99%